Faktor-Faktor yang Berpengaruh pada Corporate Social Responsibility - Dwija Putri, I Gusti Ayu Made Asri; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 32 No 12 (2022)DO - 10.24843/EJA.2022.v32.i12.p15, 2022)
Disclosure of CSR has a positive impact on company value, improves the company's reputation and brand image, thus leading to better financial performance and can reduce financial risk. This study aims to determine the effect of managerial ownership, institutional ownership, company size, return on assets, and leverage on the disclosure of Corporate Social Responsibility (CSR) in manufacturing companies on the IDX. The sample was selected by nonprobability sampling method with purposive sampling technique. The data analysis technique uses multiple linear regression analysis. The results showed that managerial ownership and firm size had a positive effect on Corporate Social Responsibility, while leverage had a negative effect on CSR disclosure. Institutional ownership and return on assets do not have a positive effect on CSR disclosure. Keywords: CSR Disclosure; Ownership Structure; Firm Size; Return on Assets; Leverage